Variation of plasma citrulline as a predictive factor for weaning off long-term parenteral nutrition in children with neonatal short bowel syndrome. Issue 8 (August 2021) - Proli, Francesco; Faragalli, Andrea; Talbotec, Cécile; Bucci, Andrea; Zemrani, Boutaina; Chardot, Christophe; Abi Nader, Elie; Goulet, Olivier; Lambe, Cécile
Summary: Background & aims: Long-term parenteral nutrition (PN) is the mainstay of the therapeutic strategy in intestinal failure (IF) due to neonatal short bowel syndrome (SBS). Our aim was to identify prognostic factors for PN weaning and to assess if measuring plasma citrulline concentrations over time could account for the intestinal adaptation in progress. Methods: This retrospective study included children with neonatal SBS with surgical measurement of the residual bowel length and repeated plasma citrulline assessments during a 4-year follow-up. The degree of IF was assessed by the PN dependency index (PN caloric intake/Resting energy expenditure). The analysis was carried out according to SBS anatomical groups: end-jejunostomy (type 1), jejuno-colic (type 2) and jejuno-ileal anastomosis (type 3). Results: Fifty-five patients (8 type 1, 27 type 2, 20 type 3) were included. None of the patients with SBS type 1, 11 (41%) with type 2 and 11 (55%) with type 3 were weaned off during the follow-up period. Plasma citrulline levels significantly increased with time in patients who were finally weaned off PN; conversely, the levels did not consistently increase in patients who were still on PN at the end of the study period. There was an inverse relationship between plasma citrulline levels and the PN dependency index. The increasing citrulline levels had a positive effect on the probability of weaning, 2.7 times higher for each point increase in citrulline. No significant effect of age and residual bowel length at baseline was found. Conclusion: The increased plasma citrulline level over time in addition to the SBS anatomical type is a reliable marker for subsequent PN weaning. The prediction of PN weaning assessed solely by the residual bowel length or a single measurement of citrulline is insufficient and should also take into account the anatomical type of SBS and repeated measurements of plasma citrulline levels.